Historia lokalna i tożsamość. Przykład miast dolnośląskich - Wiszewski, Przemysław (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The aim of this article is to investigate what role was played by referring to the local history in the space of Lower Silesian towns in shaping the identity of their inhabitants. An analysis of the names of streets, monuments as well as of policies and declarations issued by the self-government entities and activities undertaken by the inhabitants themselves indicate that both in the town space and in the identity of the inhabitants, references to the past of the nation dominate.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne